2018
DOI: 10.1097/qad.0000000000001855
|View full text |Cite
|
Sign up to set email alerts
|

Progressive lentivirus infection induces natural killer cell receptor-expressing B cells in the gastrointestinal tract

Abstract: Objective Recently, a seemingly novel innate immune cell subset bearing features of natural killer and B cells was identified in mice. So-called NKB cells appear as first responders to infections, but whether this cell population is truly novel or is in fact a subpopulation of B cells and exists in higher primates remains unclear. The objective of this study was to identify NKB cells in primates and study the impact of HIV/SIV infections. Design and Methods NKB cells were quantified in both naïve and lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…The findings in the present study supported the existence of NKB cells as an independent cell population. Phenotypically, CD3 − CD19 + cells expressing NK cell-specific markers (NKp46 or NK1.1) were found in the blood and periodontium of both humans and mice, which was consistent with the previous report which showed that CD3 − CD20 + NKG2A + phenotyping was identified as NKB cells in rhesus macaques ( 25 ). Moreover, NKB cells were systemically found, but only expand in the gastrointestinal tract during simian immunodeficiency virus infected rhesus macaques.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings in the present study supported the existence of NKB cells as an independent cell population. Phenotypically, CD3 − CD19 + cells expressing NK cell-specific markers (NKp46 or NK1.1) were found in the blood and periodontium of both humans and mice, which was consistent with the previous report which showed that CD3 − CD20 + NKG2A + phenotyping was identified as NKB cells in rhesus macaques ( 25 ). Moreover, NKB cells were systemically found, but only expand in the gastrointestinal tract during simian immunodeficiency virus infected rhesus macaques.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, NKB cells were systemically found, but only expand in the gastrointestinal tract during simian immunodeficiency virus infected rhesus macaques. However, human immunodeficiency virus infection did not induce the expansion of peripheral NKB cells in humans ( 25 ). A more recent study by Ge et al ( 26 ) suggested that alcohol increased NKB cells' proportion and serum IL-18 expression in an experimental alcoholic liver injury murine model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of these B-cell and myeloid markers on uterine ILC1s is unknown, and a recently described subset of NKB cells is controversial (S. Wang et al 2017; Kerdiles et al 2017), but might be induced in SIV and HIV infection (Manickam et al 2018). Phenotypic and functional heterogeneity of g1 ILCs has been reported across tissues (Sojka et al 2014; Robinette et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Genes associated with B-cells, or for protein turnover, antigen processing and presentation, as well as the macrophage-associated F4/80 marker are upregulated in ILC1s. The role of these B-cell and myeloid markers on uterine ILC1s is unknown, and a recently described subset of NKB cells is controversial 64 , 65 , but might be induced in SIV and HIV infection 66 . The deconvolution model we have applied here confirms that uterine g1 ILCs have expression profiles aligned with those of cell types other than NK cells and including myeloid cells.…”
Section: Disscussionmentioning
confidence: 99%